Координатно-чувствительный приемник на основе анизотропного оптикотермоэлемента - Ascheulov, A. A.; Gutsul, I. V.; Photy, V. D. (PE "Politekhperiodika", Book and Journal Publishers, 2006)
A device design based on an anisotropic optothermal element intended for radiation detection is presented. The feasibility of its use as a modulation-free, nonselective coordinate-sensitive detector is demonstrated. Such a detector makes it possible to determine the coordinates of radiant fluxes over wide spectral and dynamic ranges